Genomic signatures of fine‐scale local selection in Atlantic salmon suggest involvement of sexual maturation, energy homeostasis and immune defence‐related genes. Issue 11 (21st May 2018) - Pritchard, Victoria L.; Mäkinen, Hannu; Vähä, Juha‐Pekka; Erkinaro, Jaakko; Orell, Panu; Primmer, Craig R.
Abstract: Elucidating the genetic basis of adaptation to the local environment can improve our understanding of how the diversity of life has evolved. In this study, we used a dense SNP array to identify candidate loci potentially underlying fine‐scale local adaptation within a large Atlantic salmon ( Salmo salar ) population. By combining outlier, gene–environment association and haplotype homozygosity analyses, we identified multiple regions of the genome with strong evidence for diversifying selection. Several of these candidate regions had previously been identified in other studies, demonstrating that the same loci could be adaptively important in Atlantic salmon at subdrainage, regional and continental scales. Notably, we identified signals consistent with local selection around genes associated with variation in sexual maturation, energy homeostasis and immune defence. These included the large‐effect age‐at‐maturity gene vgll3, the known obesity gene mc4r, and major histocompatibility complex II. Most strikingly, we confirmed a genomic region on Ssa09 that was extremely differentiated among subpopulations and that is also a candidate for local selection over the global range of Atlantic salmon. This region colocalized with a haplotype strongly associated with spawning ecotype in sockeye salmon ( Oncorhynchus nerka ), with circumstantial evidence that the same gene ( six6 ) may be the selective target in both cases. The phenotypic effect of this region in Atlantic salmon remains cryptic, although allelic variation is related to upstream catchment area and covaries with timing of the return spawning migration. Our results further inform management of Atlantic salmon and open multiple avenues for future research.